The Effect of of Transformational Leadership on Employee Engagement Through Career Development on Employees of PT PLN (Persero) West Sumatra Distribution Main Unit - Shelvia Angellica; Hendrik Heri Sandi (International Journal of Economics and Management Research, 2024)
This study focuses on the influence of transformational leadership on employee engagement through career development in employees of PT PLN (Persero) West Sumatra Distribution Unit, a company that plays an important role in providing electricity in Indonesia. Although the company has made efforts to improve employee engagement, the pre-survey results show that the level of employee engagement is still low, which is the main problem in this study. The purpose of the study is to analyze the relationship between transformational leadership, career development, and employee engagement. The method used was a quantitative approach with a causal research design, involving a 76 employees as responden. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The research findings show that transformational leadership has a positive and significant influence on employee engagement and career development, and career development contributes positively to employee engagement. In addition, career development serves as a significant mediating variable in the relationship between transformational leadership and employee engagement. The conclusion of this study emphasizes the importance of implementing transformational leadership and effective career development programs to increase employee engagement, which in turn can increase productivity.